The Role of Teachers in Increasing Independence in Students With Special Needs Who are Intellectual Disabilities - Nenden Ariyani; Suyatno Suyatno; Sukirman Sukirman (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study aims to examine the role of teachers in improving the independence of students with special needs, particularly those with intellectual disabilities. Using a qualitative approach, the research explores how teachers support independence through learning strategies, individual assistance, and self-development. Data were collected through observation and interviews at an inclusive junior high school. The findings show that teachers play a significant role in developing student independence through systematic routines, such as habituation and social interaction training. Customized learning strategies include module modification, differentiated curriculum, talent development, and individual mentoring using the one-teacher-one-student model. Despite challenges like limited facilities, inadequate tools, and varying student abilities, positive outcomes were observed. Students demonstrated improved ability to complete simple tasks independently, increased self-confidence, and greater initiative in social interactions. These results underline the importance of teacher involvement, flexibility in instructional approaches, and the need for continuous collaboration between schools and families. The study highlights that with proper support and strategies, students with intellectual disabilities can develop meaningful levels of independence and participate actively in their learning environment.